2004
DOI: 10.1182/blood-2003-07-2214
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) induces rapid prourokinase (pro-uPA) activation on the surface of endothelial cells

Abstract: Vascular endothelial growth factor (VEGF) is the pivotal angiogenic growth factor activating endothelial cells to migrate, proliferate, and form capillary tubes. For an ordered endothelial cell migration, tissue invasion, and degradation of the extracellular matrix, proteolytic machinery is indispensable. Such machinery, suitable for localized proteolysis, is provided by the prourokinase-urokinase-plasmin system. Prourokinase (pro-uPA), the initial component of this system, is, however, synthesized in its inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 32 publications
6
112
1
Order By: Relevance
“…44 During migration, VEGF-A induces pro-uPA activation via KDR/ Flk-1, and uPAR internalization leads to increased fibrinolytic activity in endothelial cells. 45 Furthermore, increased uPAR expression by hypoxia is enhanced in migrating endothelial cells in vitro, 46 and the finding that neovascularization of transplanted tumors in vivo is inhibited by uPAR antagonists 47,48 suggests that hypoxia-stimulated uPAR expression plays an essential role in tumor metastasis as well as local invasion. In our experiments, HUVECs stimulated with VEGF-A displayed elevated levels of uPA and uPAR proteins, and emodin inhibited the VEGF-Ainduced expression of uPAR, but not of uPA.…”
Section: Discussionmentioning
confidence: 99%
“…44 During migration, VEGF-A induces pro-uPA activation via KDR/ Flk-1, and uPAR internalization leads to increased fibrinolytic activity in endothelial cells. 45 Furthermore, increased uPAR expression by hypoxia is enhanced in migrating endothelial cells in vitro, 46 and the finding that neovascularization of transplanted tumors in vivo is inhibited by uPAR antagonists 47,48 suggests that hypoxia-stimulated uPAR expression plays an essential role in tumor metastasis as well as local invasion. In our experiments, HUVECs stimulated with VEGF-A displayed elevated levels of uPA and uPAR proteins, and emodin inhibited the VEGF-Ainduced expression of uPAR, but not of uPA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, does activation of MMPs occur simultaneously or subsequently to integrin activation? Some studies have indicated that the activation of the proteases may occur concomitant with integrin ligand-binding and activation (Prager et al, 2003;Yan et al, 2000). Investigations with activation state-specific integrin antibodies and antibodies specific for pro-and active MMPs could shed light on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 (trypsin-activated) yes (Crabbe et al, 1994) Pro-MMP-2 yes (Crabbe et al, 1993) Pro-MMP-9 yes yes (Fridman et al, 1995;Ray et al, 2003) Pro-MMP-13 yes (Knauper et al, 1996) Pro-TGF-β1 yes yes (Yu and Stamenkovic, 2000) Pro-TNF-α yes yes (Gearing et al, 1994) Pro-urokinase yes (Prager et al, 2003) Stromal cell derived factor (SDF)-1 yes yes (McQuibban et al, 2001) Substance P yes (Backstrom and Tokes, 1995) Troponin yes Urokinase receptor yes no (Andolfo et al, 2002) Gelatinase binding to native collagens and gelatin occurs primarily via the CBD (Allan et al, 1995), whereas other MMPs, eg. MMP-3 utilizes the C-terminal domain for collagen binding (Allan et al, 1991).…”
Section: (Van Den Steen Et Al 2000)mentioning
confidence: 99%
See 2 more Smart Citations